Determination of free glycerol in biodiesel at a platinum oxide surface using potential cycling technique - Lourenco, Leandro Maranghetti [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2009)
A novel, inexpensive and fast method based on the electrooxidation of glycerol on platinum electrodes by the potential cycling technique has been designed for the determination of free glycerol in biodiesel. A wide range of linearity was achieved between 15 and 150 mg L(-1) (0.16 and 1.6 mmol L(-1)), which corresponds to concentrations ranging between 56 and 560 mg kg(-1) (glycerol: biodiesel) for an extraction using 2g biodiesel. A method for the fast extraction of glycerol from biodiesel with water followed by elimination of organic interferents has also been developed, so that the novel determination method can be applied to various biodiesel samples. The excellent repeatability allows determination of glycerol in numerous samples, with no need for recalibration. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; Free glycerol; Platinum; Potential cycling technique; Cyclic voltammetry; Quality control